Teacher Content Knowledge and Use of Instructional Materials as Catalysts for English Reading Comprehension Instruction in Secondary Schools (2023)
This study investigated teacher pedagogical content knowledge and use of instructional materials as correlates of achievement in English reading comprehension. The correlational design was adopted.The simple random sampling technique was used to select 10 public secondary schools and 500 students (50 per school) in Ibadan North Local Government Area. The instruments used were English language achievement test(r=0.78), Teacher Use of Instructional Materials(r=0.75), and Teacher Content Knowledge(r=0.82) rating scales. Data were analyzed using Pearson product moment correlation and multiple regression at 0.05 level of significance. There was a negative relationship between students'achievement in English reading comprehension and teacher content knowledge but it has positive moderate relationship with instructional materials. The joint contribution of the three independent variables to achievement in English reading comprehension was not significant. The relative contribution of the independent variables to student achievement in English reading comprehension was not significant. These variables should be taken into consideration to improve learning outcomes in English language